IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI PEMBELAJ RAN PAI DALAM MENGHADAPI TANTANGAN DI ERA DIGITAL - Amanda Rofina; Bahar Agus Setiawan; Dhian Wahana Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Character education become the main priority in the field of education during the rapid advancement of digital technology. In this case, Islamic Education (PAI) has an important role in instilling moral values so that students can wisely face the challenges of the digital era. Accordance with Thomas Lickona’s theory whic h covers many aspects moral knowing, moral feeling, and moral action as well as the concept of digital literacy in education. Based on this background, this research focused on the research question is how the Implementation of character education through Islamic Education Learning (PAI) to face challenges in the digital era. This research is aimed to determine the implementation of character education through Islamic Education (PAI) in facing the challenges of the digital era, and analysing the role of Islamic Education to instil student’s character education.This research employs a qualitative approach using a case study that conducted at SMP Negeri 1 Asembagus. The data collection was conducted through interviews, observations, and documentations with the involvement of school principal, Islamic Education (PAI) teacher, and students as the research informants. The data collected then analysed through the step of data condensation, data presentation, and conclusion. The research finding showed that the character education is implemented through the integration of character values into the Islamic Education (PAI) learning process, the use of active learning methods such as role playing, and the cultivation of religious behaviours and moral attitudes in daily life, including through the use of digital media. Although the challenges posed by environmental factors at school, the teachers still continue to implement various strategies to deal with them. Thus, Islamic Education has a role in shaping students’ character so that they are able to face the challenges of digital era in a critical and responsible way, based in moral values.